(untitled) (Journal of Asian Development Studies, 2021)
All over the world, particularly developing countries have understood the importance of SMEs as responsible for accommodating many unemployed, thus acting as an income generating platform. In SMEs, exporting is a way to get quick access to markets abroad and provides opportunity to achieve valuable international exposure. The objective of this study is to detect the relationship between entrepreneurial orientation (EO) of internationalized SMEs (born international) and their export performance in the surgical instruments manufacturing and exporting industry in Pakistan. Survey questionnaire is used to collect data from the firms. Entrepreneurial orientation was measured using five dimensions and export performance is measured using three dimensions. Purposive sampling is used to draw sample from population where the unit of analysis is born international firms. The findings of the study show that entrepreneurial orientation exists in the born international firms. Regarding measuring export performance, the result shows that the firm exhibit export performance to a good extent. It has been concluded that there is correlation between entrepreneurial orientation and export performance.